Alveolar echinococcosis in immunocompromised hosts. (May 2023) - Autier, Brice; Gottstein, Bruno; Millon, Laurence; Ramharter, Michael; Gruener, Beate; Bresson-Hadni, Solange; Dion, Sarah; Robert-Gangneux, Florence
Abstract: Background: Alveolar echinococcosis (AE) results of an infection with the larval stage of Echinococcus multilocularis . It has been increasingly described in individuals with impaired immune responsiveness. Objectives: This narrative review aims at describing the presentation of AE according to the type of immune impairment, based on retrospective cohorts and case reports. Implications for patient management and future research are proposed accordingly. Sources: Targeted search was conducted in PubMed using ((alveolar echinococcosis) OR (multilocularis)) AND ((immunosuppressive) OR (immunodeficiency) OR (AIDS) OR (solid organ transplant) OR (autoimmunity) OR (immune deficiency)). Only publications in English were considered. Content: Seventeen publications were found, including 13 reports of 55 AE in immunocompromised patients (AE/IS) and 4 retrospective studies of 755 AE immunocompetent patients and 115 AE/IS (13%). The cohorts included 9 (1%) solid organ transplantation (SOT) recipients, 2 (0.2%) HIV patients, 41 (4.7%) with chronic inflammatory/autoimmune diseases (I/AID) and 72 (8.3%) with malignancies. SOT, I/AID and malignancies, but not HIV infection, were significantly associated with AE (odds ratios of 10.8, 1.6, 5.9, and 1.3, respectively). Compared to AE immunocompetent patients, AE/IS was associated with earlier diagnosis (PNM stages I–II: 49/85 (58%) vs. 137/348 (39%), p < 0.001), high rate of atypical imaging (24/50 (48%) vs. 106/375 (28%), p < 0.01), and low sensitivity of serology (19/77 (25%) vs. 265/329 (81%), p < 0.001). Unusually extensive or disseminated infections were described in SOT and I/AID patients. Implications: Patients who live in endemic areas should benefit from serology before onset of a long-term immunosuppressive therapy, even if the cost-benefit ratio has to be evaluated. Physicians should explain AE to immunocompromised patients and think about AE when finding a liver lesion. Further research should address gaps in knowledge of AE/IS. Especially, extensive and accurate records of AE cases have to be collected by multinational registries.